PENILAIAN KINERJA PEGAWAI NEGERI SIPIL DI BADAN KEUANGAN DAN ASET DAERAH KABUPATEN GORONTALO - Debriyana Adam; Arifin Tahir; Zuchri Abdussamad (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This research aims to analyze the performance assessment of civil servants (PNS) at the Regional Finance and Assets Agency of Gorontalo Regency. Performance assessment is a key element in effective human resource management, and is important to ensure that this policy is implemented correctly in order to improve organizational performance in Gorontalo district's regional financial and asset bodies. There are several supporting factors such as commitment from regional leaders and support from central government policies. This research method uses descriptive qualitative. Data collection techniques were carried out using observation, interviews and documentation. Data analysis techniques begin data collection, data reduction, data display and drawing conclusions or verification.The research findings show that the Civil Servant Performance Assessment at the Gorontalo Regency Regional Finance and Assets Agency is effective and efficient.